MiRNA-155 Regulates the Th17/Treg Ratio by Targeting SOCS1 in Severe Acute Pancreatitis - Wang, Dongyan; Tang, Maochun; Zong, Pengfei; Liu, Hua; Zhang, Ting; Liu, Yu; Zhao, Yan (Frontiers in Physiology, 2018)
Acute pancreatitis (AP) is a serious condition associated with intestinal barrier disruption or inflammation of the pancreatic tissue. Specific microRNAs are involved in the pathogenesis of AP, during which IL-17-producing CD4+ T helper (Th17) cells accumulate in the pancreas. In this study, significantly increased levels of miR-155 were detected in clinical samples from patients with AP, and overexpression of miR-155 correlated with severe AP (SAP). To identify the effect of miR-155 on T cell differentiation, we isolated CD4+ T lymphocytes and in vitro experiments showed that inhibition of miR-155 significantly reversed the stress-induced increase in the Th17/Treg ratio. The results also showed that miR-155 increased the Th17-mediated inflammatory response by targeting SOCS1. The interaction between miR-155 and the 3ʹUTR of SOCS1 was confirmed by a dual luciferase reporter assay and RT-PCR. Experimental AP of varying severity was induced in BALB/c mice by caerulein hyperstimulation and miR-155 expression was found to increase with disease progression. Inhibition of miR-155 expression significantly improved the pathology of the pancreas. We also observed downregulation of expression of inflammatory factors, IL-17, SOCS1 and phosphorylated STAT1 after miR-155 inhibition. In summary, miR-155 regulates the Th17/Treg ratio by targeting SOCS1, most probably via direct binding to its 3'UTR region, indicating that this microRNA may be a potential biomarker and/or therapeutic target for AP.